2012
DOI: 10.1037/a0024555
|View full text |Cite
|
Sign up to set email alerts
|

Putting the social into social learning: Explaining both selectivity and fidelity in children's copying behavior.

Abstract: Many previous accounts of imitation have pointed out that children's copying behavior is a means by which to learn from others, while virtually ignoring the social factors which influence imitation. These accounts have thus far been unable to explain flexibility in children's copying behavior (e.g., why children sometimes copy exactly and sometimes copy selectively). We propose that the complexity of children's imitation can only be fully understood by considering the social context in which it is produced. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
310
1
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(337 citation statements)
references
References 91 publications
(172 reference statements)
19
310
1
7
Order By: Relevance
“…From a young age, children acquire stereotypes about social groups and are motivated to conform to members of their ingroup and of the majority consensus (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Both of these aspects of social cognition rely on an expectation that social group members act alike.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a young age, children acquire stereotypes about social groups and are motivated to conform to members of their ingroup and of the majority consensus (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Both of these aspects of social cognition rely on an expectation that social group members act alike.…”
Section: Discussionmentioning
confidence: 99%
“…Socially motivated imitation or conformity and stereotyping share an early developmental onset (7,8). Many cultural behaviors, including social gestures and language, are acquired in the first few years, suggesting early biases for adopting the typical behaviors of one's own social group.…”
mentioning
confidence: 99%
“…The function of imitation for the child at the moment of the demonstration is important in determining which aspect of a demonstration the child is likely to copy (Carpenter, 2006;Over & Carpenter, 2012). Although the cognitive function and the social function co-occur, the cognitive function might become more apparent when infants are presented with novel object-related actions.…”
Section: Introductionmentioning
confidence: 99%
“…The term overimitation is used to describe instances in which children imitate actions even when those actions are irrelevant to the task at hand (e.g., Horner and Whiten 2005;Nagell et al 1993;Nielsen 2006). One reason that children are thought to engage in overimitation is out of a desire to connect socially with another person (Carpenter 2006;Nielsen 2006;Nielsen and Carpenter 2008;Over and Carpenter 2012;Tomasello et al 2005). Watson-Jones et al (2014) found that when primed with a video demonstrating ostracism as opposed to affiliation, children engaged in imitative behaviors that adhered more closely to the modeled behavior.…”
Section: Social Motivation and Imitationmentioning
confidence: 99%